Internet Access, Electricity Access, and Education Implications for MSMEs Productivity in Indonesia: Evidence from Dynamic Panel GMM - Fitrianingsih, Arina; Basuki, Agus Tri; Dewanti, Diah Setyawati (Journal of Economics Research and Social Sciences, 2026)
This paper examines the relationship between access to digital infrastructure, basic utilities, and human capital and the productivity of Micro, Small, and Medium Enterprises (MSMEs) across Indonesian provinces using panel data from 2020 to 2024. A dynamic panel data approach employing the Arellano–Bond Generalized Method of Moments estimator is used to control for regional heterogeneity and address endogeneity issues. The results indicate that access to electricity is positively correlated with MSME productivity in the short run, highlighting its role as a basic precondition for the smooth operation of daily business activities. In contrast, access to the internet does not significantly affect MSME productivity in the short run, suggesting that digital readiness requires sufficient time for adaptation to translate into productivity gains. Moreover, average years of schooling are negatively correlated with short-run MSME productivity, potentially reflecting a transitional effect as more educated individuals are more likely to move toward formal employment. Diagnostic tests confirm the robustness of the results, with no evidence of weak instruments or second-order serial correlation. Overall, the findings suggest that while improvements in electricity access are important for short-run MSME productivity, long-run regional productivity differences are more strongly influenced by digital readiness and the effective deployment of human capital within the MSME sector. Accordingly, policy interventions should extend beyond the provision of basic utilities and focus on enhancing digital readiness and the effective utilization of human capital.